Australia, 1803
Includes letters from: Rowland Hassell, Parramatta [Sydney] Samuel Marsden, Parramatta - in communication with Tahiti (peaceful); purchase of animals and seeds; testimonial to John Harris Philip King (governor of New South Wales), Sydney - mail William Crook, St Sebastian [South Africa] and Port Philip [Melbourne]